2017
DOI: 10.1145/3044534
|View full text |Cite
|
Sign up to set email alerts
|

WaitSuite

Abstract: The busyness of daily life makes it difficult to find time for informal learning. Yet, learning requires significant time and effort, with repeated exposures to educational content on a recurring basis. Despite the struggle to find time, there are numerous moments in a day that are typically wasted due to waiting, such as while waiting for the elevator to arrive, wifi to connect, or an instant message to arrive. We introduce the concept of wait-learning: automatically detecting wait time and inviting people to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…And just what is rewarding at the moment is independence" (P13). This fnding is in line with research that shows that interruptions which do not occlude the primary task generally are perceived to be less mentally demanding and less annoying [1,11,14]. P2 described in their interview that they did not have a specifc use case in mind for learning Python, they just believed it might be a useful thing to know.…”
Section: Learning Imposes Cognitive Demand (Rather Than a Break)supporting
confidence: 77%
See 2 more Smart Citations
“…And just what is rewarding at the moment is independence" (P13). This fnding is in line with research that shows that interruptions which do not occlude the primary task generally are perceived to be less mentally demanding and less annoying [1,11,14]. P2 described in their interview that they did not have a specifc use case in mind for learning Python, they just believed it might be a useful thing to know.…”
Section: Learning Imposes Cognitive Demand (Rather Than a Break)supporting
confidence: 77%
“…Cai et al introduced the concept of wait-learning, where a digital system automatically detects when a person is waiting, and ofers them a "productive opportunity" to learn language. Their users described system-triggers as important to help them form a habit [14].…”
Section: Goal Advancementmentioning
confidence: 99%
See 1 more Smart Citation
“…An instructional design with one idea at the time avoids excessive cognitive load (Paul, 2016). The presentation of small learning units in spaced intervals assures adaptation to an individual's learning curve, also making it possible to learn in otherwise unproductive waiting moments (Cai et al, 2017). Microlearning is usually comparably inexpensive and easy to customize for the respective business (Scaglione, 2019).…”
Section: Microlearningmentioning
confidence: 99%
“…L2 vocabulary microlearning has also been investigated with an app that leverages user location data (Edge et al, 2011); with passive exposure to vocabulary and collocated phrases via an automatically updated wallpaper screen on the user's mobile device (Dearman & Truong, 2012); with an Internet browser extension that overlays L2 words on first language website content (Trusty & Truong, 2011); with a system that inserts interactive vocabulary quizzes into the user's social media feed (Kovacs, 2015); and with machine learning (natural language processing) to offer vocabulary practice that is embedded into the learner's daily life (Arakawa et al, 2022). L2 vocabulary microlearning has been inserted in the time wasted while people are waiting for an elevator, an instant message reply, or a wi-fi connection (Cai et al, 2015(Cai et al, , 2017. Zhao et al (2018) even suggested using smartwatches for L2 vocabulary learning.…”
Section: Microlearning and Peer Feedback Appsmentioning
confidence: 99%